ECO-HARMONY VS ECONOMIC EQUITY - Manninezhath, Thomas (Journal of Dharma, 1993)
Philosophers and theologians,' scientists and statesmen, religious leaders and people of all disciplines earnestly discuss about the decisive question of the protection of our planet, the Mother Earth. Human consciousness, therefore, is in the process of becoming more and more aware of the environmental ethics and ecology. There 'are a number of crucial ethical and economic issues involved in the 'environmental decisions we take at various national and international summits .and conferences. Journal of Dharma takes up in this number one of such Significant issues - Eco-harmony Vs Economic Equity - for analysis and this may help our readers for further 'research, reflection and action.